2009
DOI: 10.1038/cr.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis PARAQUAT RESISTANT2 gene encodes an S-nitrosoglutathione reductase that is a key regulator of cell death

Abstract: Metabolism of S-nitrosoglutathione (GSNO), a major biologically active nitric oxide (NO) species, is catalyzed by the evolutionally conserved GSNO reductase (GSNOR). Previous studies showed that the Arabidopsis GSNOR1/ HOT5 gene regulates salicylic acid signaling and thermotolerance by modulating the intracellular S-nitrosothiol level. Here, we report the characterization of the Arabidopsis paraquat resistant2-1 (par2-1) mutant that shows an anti-cell death phenotype. The production of superoxide in par2-1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
169
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(175 citation statements)
references
References 65 publications
3
169
0
3
Order By: Relevance
“…Mutation in PHB3 abort NO accumulation but does not affect H 2 O 2 signaling. Further substantiating the link between ROS and NO during cell death is the recent positional cloning of PARAQUAT RESISTANT2 gene in Arabidopsis, which encodes an S-nitrosoglutathione reductase (Chen et al 2009). Positional cloning of the atr mutants will help to understand the intricate mechanisms of cell death tolerance in Arabidopsis.…”
Section: Molecular Analysis Of Mutants Exposed To At-induced Oxidativmentioning
confidence: 99%
“…Mutation in PHB3 abort NO accumulation but does not affect H 2 O 2 signaling. Further substantiating the link between ROS and NO during cell death is the recent positional cloning of PARAQUAT RESISTANT2 gene in Arabidopsis, which encodes an S-nitrosoglutathione reductase (Chen et al 2009). Positional cloning of the atr mutants will help to understand the intricate mechanisms of cell death tolerance in Arabidopsis.…”
Section: Molecular Analysis Of Mutants Exposed To At-induced Oxidativmentioning
confidence: 99%
“…NO overaccumulates in Arabidopsis gsnor1(S-nitrosoglutathione reductase 1)/hot5 (sensitive to hot temperatures 5)/par2 (paraquat resistant 2) mutant plants that are impaired in the GSNO reductase gene (32)(33)(34). The gsnor1-3 mutant is hypersensitive to heat stress (33) and bacterial pathogen (28,31), but is more resistant to oxidative stress (34).…”
mentioning
confidence: 99%
“…This study provided evidence that SNO metabolism controlled by GSNOR had a key role in plant disease resistance. Further studies have since revealed that GSNOR appears to be a key regulator of cell death (9) and is also required for thermotolerance (22). Various studies discussed in the following section have also shown that S-nitrosylation of specific proteins is increased in gsnor1-3 mutant plants.…”
Section: S-nitrosoglutathione-reductase and S-nitrosylationmentioning
confidence: 92%